The Effectiveness of Murottal Al-Qur’an Therapy by Surah Ar-Rahman toward Anxiety of Crhonic Kidney Disease (CKD) which is being Hemodialysis at Gambiran Hospital Kediri - Byba Melda Suhita; Dini Yulianita Arini; Dhita Kurnia Sari; Sri Kardjati (Universitas STRADA Indonesia, 2019)
ABSTRACT Chronic kidney disease is a decrease in the function of kidney which is caused by a process of irreversible damage, thus requiring hemodialysis therapy as a replacement therapy for the function of kidney. Hemodialysis patients often experience psychosocial problem. It is an anxiety. This research aims to analyze the effectiveness of Murottal Al-Qur’an therapy by surah Ar-Rahman toward anxiety of Chronic Kidney Disease (CKD) which is being hemodialysis. The research was conducted at Gambiran Hospital Kediri. The research used Quasi Experimental with a control group pretest-posttest design approach with samples using simple random sampling of 58 respondents. Paired sample t-test was used to analyze the data by a value of α = 0.05.